Keep all mobile users′ whereabouts secure: a radio frequency identification protocol anti‐tracking in 5G. (8th April 2015) - Yin, Xi; Fang, Binxing; Jin, Shuyuan; Qiu, Meikang; Vasilakos, Athanasios V.; Xu, Yongjun
Summary: In the fifth generation mobile networks (in short, 5G), radio frequency identification (RFID) tags are embedded in a growing number of personal items, especially in smartphones. The RFID authentication protocols in 5G should be anti‐scanning and privacy‐enhancing, because RFID tags in smartphones often suffer from leaking private trace of mobile users. However, majorities of existing RFID protocols are vulnerable to location‐tracking threats, and to distributed denial of service (DDoS) attacks on back‐end servers. To eliminate these threats, we propose a hash‐based mutual authentication protocol for smartphones in 5G. This protocol protects individuals' location privacy against malicious hidden scanning in public places. By the authentication of RFID readers via hash values, the proposed protocol is robust against the aforementioned threats. Additionally, our authentication efficiency on the tag side is 2H (two hash calculations), which outperforms most of previously reported solutions based on hash, and the tag stores only two vectors (one is k ‐bit and the other j ‐bit). Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Our goal is protecting mobile users' location privacy against unauthorized hidden radio frequency identification scanning in public places in 5G. We have proposed a novel hash‐based mutual authentication protocol, which is secure against location‐tracing attacks. Furthermore, our protocol prevents tracing previous routes of the tag in public places, after physical corruption of the tag. Additionally, our protocol has successfully overcome distributed denial of service attacks on back‐end servers and reduced the delay and energy consumption on the tag side to only two hash calculations.